Digital File Identification Method Using Efficient Anonymous Fingerprinting: Digital File Identification Method Using Efficient Anonymous Fingerprinting - Agustina Simangungsong (Jurnal Mantik, 2019)
Fingerprinting method is one important class of engineering protection of intellectual property in digital form. This method is a cryptographic method that is applied to detect people to redistribute an item of data by allowing a merchant (merchant) to track a duplicate to be able to note the original purchaser. Buyers dishonest redistribute illegally item of data called a traitor (traitor). Information referred to as fingerprint identification, attached to the duplication of the original item data. For the development of an application it is necessary to illustrate the application of anonymous fingerprinting methods in the detection of identity of the file redistributed. Other than that, the software also provides a tutorial to assist understanding of the working procedures of anonymous fingerprinting method. The results of the tutorial section can also be saved into a text file.